Quality Early Learning : Nurturing Children's Potential - Bendini, Magdalena; Devercelli, Amanda E. (Washington, DC: World Bank, 2022)
In this volume, leading researchers and implementation experts from an array of disciplines provide evidence-based, cost-effective, and actionable strategies for delivering quality early childhood education (ECE) at scale in low- and middle-income countries (LMICS).Over the past decade, neuroscientists, developmental and cognitive psychologists, economists, and education researchers have amassed evidence to inform ECE program design. Yet much of this evidence has not been readily accessible to policymakers and practitioners, and potential synergies from cross-disciplinary considerations have not been realized.Quality Early Learning: Nurturing Children’s Potential synthesizes the evidence across disciplines and charts a forward course for quality ECE. The volume includes